THE ROLE OF FOLKLORE IN LANGUAGE TEACHING AND LEARNING PROCESS (Academicia Globe: Inderscience Research, 2023)
This article discusses certain peculiarities of using folklore units in FLT process, step by step analysis of the use of folk stories to different level of language learners. It is stated that to be fully aware or fluent in one language a learner should know cultural traits of the foreign language to be taught. This may help them practice the real native foreign life. Depending on the level of our students, the choice of folklore types can be changed. The high availability of folk literature may lead to productive English teaching classes.